ANALISAHUKUM TERHADAP STRATEGI DAN PENGEMBANGAN USAHA MIKRO KECIL MENENGAH (UMKM) PRODUKSI GULA AREN SEMUT DI KABUPATEN LEBAK - Sulasno; Inge Dwisvimiar (LPPM STIA Banten, 2023)
Business actors in this micro, small and medium enterprises (MSMEs) are one of the business fields that can develop and be consistent in the national economy. Micro, small and medium enterprises (MSMEs) are a good platform for job creation planned by the government, the private sector and individual business actors. This study aims to identify, understand and analyze the strategy for developing ant palm sugar at CV Sari Aren Mandiri, Cihara Village, Panggarangan District, Lebak Regency. Besides that, they also know about legal protection for MSME products. The research method is a qualitative descriptive method. Data collection techniques used were observation, interviews, and documentation. The results showed that the development strategy carried out by CV Sari Aren Mandiri carried out existing developments, namely innovation, Intellectual Property, Typical, barcode, BPOM, Halal Product quality. In addition, those related to preventive and repressive legal protection.